An epidemiological study of a Schistosoma intercalatum focus in south-east Gabon - Martin-Prével, Yves; Berteau, Frédéric; Bouyssou, Michel; Ripert, Christian; Pinder, Margaret (Transactions of the Royal Society of Tropical Medicine and Hygiene, 1992)
A Schistosoma intercalatum focus in south-east Gabon was studied between July 1989 and July 1990. Among the 356 permanent residents in the village, 354 provided stool specimens and 101 (28·5%) were excreting eggs (geometric mean of egg density = 101 · 4 eggs/g, with a range of 1–3200). The pattern of prevalence and intensity of infection with age showed the curve usually found in schistosomiasis, i.e. increasing during the first 2 decades of life and then gradually decreasing. The analysis by stepwise logistic regression of factors shown to be important in determining infection in other schistosomiases clearly demonstrated the significant and independent effects of both age and water contact on infection by S. Intercalatum. These similarities with other schistosomal infections could indicate that similar immune mechanisms were operating. Urine from 284 subjects, of whom 90 were egg excreters, was tested for circulating antigen by enzyme-linked immunosorbent assay using a Schistosoma genus-specific monoclonal antibody (Sm 10·27·12). The test was positive for 90 subjects but only 35 of these were egg excreters. Although S. intercalatum is usually considered of low pathogenicity in man, this study showed a relationship between egg excretion and both splenomegaly and lower haemoglobin levels, even after taking into account the confounding presence of Plasmodium falciparum.